Recent advances in biopolymeric antioxidant films and coatings for preservation of nutritional quality of minimally processed fruits and vegetables. (December 2021) - Khan, Muhammad Rehan; Di Giuseppe, Fabio Angelo; Torrieri, Elena; Sadiq, Muhammad Bilal
Highlights: Nutritional quality losses in F&V are caused by reactive oxygen species and oxidative enzymes. Around 5–30 % losses of ascorbic acid and phenolic compounds occur from oxidation reactions. Standardization of analytical tests is required to compare antioxidant capacity of the active films. Active coatings enriched with natural compounds can maintain nutritional quality of the F&V. Safety, toxicity and allergenicity are critical regulation issues for active coating application. Abstract: Minimally processed F&V while being as fresh as the intact product, are characterized by an accelerated produce decay which affects its nutritional value during shelf-life. In this sense, food processing needs to further evolve in terms of better preservation of nutritional properties. Active packaging technology has shown positive and promising results to maintain safety and sensory properties of minimally processed F&V. This review aims to present the recent research results regarding biopolymeric antioxidant film and coating for preservation of nutritional quality of minimally processed F&V. The mechanism by which nutritional losses (around 5–30 % loss of ascorbic acid and phenolic compounds) occur from oxidation reactions in F&V and natural antioxidant have been discussed. Furthermore, regulatory aspects related to antioxidant packaging have been also reported. Biopolymers based antioxidant film and coating have been vastly used to pack F&V product. Chitosan, gelatin, casein and alginate were found to be more effective as packaging materials (both as coating and as film) to preserve the nutritional and sensory quality of F&V product. Furthermore, plant extracts (green tea and Aloe vera), essential oils (lemon grass), plant oil compounds (eugenol and citral) and phenolics (thymol) as a component of active film or coating systems have shown promising results in preserving the quality of fresh produce. The collected findings will be useful to accurately design an innovative active film or coating for nutritional quality preservation of minimally processed fresh fruits and vegetables.